Level of inhaler technique knowledge and its association with duration of service in primary care among medical officers in Peninsular Malaysia - Rahmat, Rofaizal Rahmat (2018)
Level of Inhaler Technique Knowledge and Its Association with Duration of Service in Primary Care Among Medical Officers in Peninsular Malaysia Background: Aerosol medicine (inhaler) used in treatment of chronic airway diseases (i.e. Chronic Obstructive Pulmonary Disease and asthma) comes either in the form of mist/spray or dry powder, which are delivered to the lungs via various design of devices. Inhaler medicine requires a complex technique which may differ based on the devices to enable the drugs to reach the lungs. Ineffective technique may affect the delivery of drugs to the lungs, and patients are always having poor technique as proven in many studies. Thus, it is important for medical officers to have adequate inhaler technique knowledge, as they are the responsible for patient’s assessment and education of inhaler use. The current study was thus conducted to ascertain the depth of inhaler technique knowledge of medical officers in primary care centres. Objective: To study the level of inhaler technique knowledge among medical officers and its association with duration of service in primary care. Methodology: A cross-sectional study was done in 2017 among medical officers at primary care in Peninsular malaysia involving three states (Selangor, Kedah and Kelantan). Self -administered questionnaires were distributed to the respondents. The questionnaire enquires on sociodemographic data, background on clinical experience, knowledge on inhaler technique and practice on reviewing patient’s inhaler technique. Data entry and analysis was performed using SPSS version 24. Result: The questionnaire was completed by 122 medical officers. The mean age of respondent was 33 years with most respondents was female doctors (n=107, 87.7%). Regarding clinical experience, the duration of service in primary care was on average 7 years with frequency of prescribing inhaler of 5 times in a month. The mean score on inhaler technique knowledge questions among the respondents only was 12 marks out of 22. Further analysis using ANCOVA showed that there was no significant effect of duration of service in primary care on inhaler technique knowledge score after controlling the effect of inhaler prescribing frequency with adjusted mean difference - 0.727(1.693,0.240), F(1,120)=2.21, P= 0.132. Conclusion: In the present study, the inhaler technique knowledge among medical officers in primary care was not at the expected level. Furthermore, there was no association between the duration of service in primary care and the level of inhaler technique knowledge. Possible intervention like in-service training regarding inhaler devices according to the guidelines may lead to improvement in the knowledge among the primary care medical officer.